Visibility and Malaysian Scholarly Journals - Zainab, A.N.; Nor, B.A. (2008)
This paper approached journal visibility in two ways: (a) the presence or visibility of Malaysian journals in internationally oriented Online databases as it is assumed that such presence would make the journal accessible and visible to the global academic community, and (b) the presence of Malaysian journals on the Web as it is assumed that electronic presence will also make the journal visible to the increasingly “wired” educational community. The former evaluates the performance of Malaysian journals in selective databases such as the ISI and SCOPUS databases and the subject-based indexing and abstracting databases. The development of MyAIS (Malaysian Abstracting and indexing system) is described. The later assessed the growth of Malaysian electronic journals, which is seen as a viable method of making Malaysian scholarly works more visible on the web. The advantages of publishing electronically and on open access, as well as the possibility of publishing in an e-journal host, EJUM (Electronic Journal University of Malaya) is described.